ChemInform Abstract: Noncentrosymmetric Cubic CsCdBO3 with Bichromophore. Issue 2 (14th January 2014) - Yu, Hongwei; Wu, Hongping; Pan, Shilie; Zhang, Bingbing; Wen, Ming; Yang, Zhihua; Li, Hongyi; Jiang, Xiangzhan
Abstract Single crystals of the title compound are obtained from a molten mixture of Cs2CO3, CdO, and H3BO3 (1:1:2 molar ratio, Pt crucible, 800 °C, 10 h).